A Randomized Controlled Trial Comparing Sequential with Triple Therapy for Helicobacter pylori in an Aboriginal Community in the Canadian North - Amy L Morse; Karen J Goodman; Rachel Munday; Hsiu-Ju Chang; John Morse; Monika Keelan; Janis Geary; Sander Veldhuyzen van Zanten; CAN Help Working Group (Canadian Journal of Gastroenterology)
BACKGROUND: Helicobacter pylori infection occurs more frequently in Arctic Aboriginal settings than elsewhere in North America and Europe. Research aimed at reducing health risks from H pylori infection has been conducted in the Aboriginal community of Aklavik, Northwest Territories.